Obstruction in Mobility of Urban Dwellers A study on vehicle handling and road using practices of Kathmandu - Sigdel, Bhim Raj (Journal of Development Review, 2023)
This study deals with two questions: Why have vehicle handling and road practices created constraints in smooth mobility of people in Kathmandu? And, what are the social causes of mobility obstruction of people on road in Kathmandu? Obstruction in mobility is a socially created problem since it is closely related to vehicle handling practices (traffic rules breaking and social behaviors against handling system and road practice) in city area. The causes of an obstruction of people’s mobility in roadside are not narrow road and over vehicles but rather our wrong vehicle handling and road using practices. Social practice is one of the significant indicators that reflects situation of development of any societies. Often every society considers either its practice is the best or expects to be the best. But some practices of particular society contribute to run society positively; some contribute to hinder the positive change. Although vehicle handling is a physical issue, it has been impacting in the mobility of people and their daily life activities which have converted it as a social issue. The very vehicle handling practices are conditioned by our historical and social structure. Based on the empirical observations of ongoing vehicle handling practices, this paper examines how these practices are creating problems in people’s smooth move and hampering their daily routine-works. Finally it argues that the claim that the lack of infrastructure and weak intervention of concerned law are the causes of obstructions for smooth move and execution of daily routine-works are myths. The activities related to vehicle handling such as stopping in non-stop areas, lane disobeying, unnecessarily over taking, parking violation, avoiding and abusing traffic police, ignoring zebra cross, over (unlimited) speed etc. are developed as mal-practices in vehicle handling sectors which have been creating obstructions in smooth mobility of people in Kathmandu because of the execution of flexible and unfixed laws, low amount of penalty or no penalty in some cases concerning to vehicle handling practices and lack  of knowledge about smart and advance practices of urban lives.